Hubungan Tugas Kesehatan Keluarga Dengan Kadar Glukosa Darah Pada Lansia Diabetes Melitus - Tyas Aulia Hanani; Diah Ratnawati (JURNAL INFO KESEHATAN, 2019)
Elderly as an individual who is at risk of encountering health problems such as diabetes mellitus because the body's functional decline requires a family health task in the form of controlling blood glucose levels that are expected to be able to overcome the problem of diabetes mellitus for the elderly. The objective of this study is to determine the relationship of the implementation of family health tasks with controlling blood glucose levels on the elderly. The research design used was descriptive-analytic with a cross-sectional approach. The population of the families who cared for and lived with elderly suffering from diabetes who are older than 60 years was 136 families, so the researchers determined the sample based on a minimum sample using the Slovin formula. The samples obtained were 102 respondents selected by the stratified random sampling method. The univariate analysis used frequency proportions, and bivariate analysis used the chi-square test. The results of this study indicate that there was a relationship between the implementation of family health tasks with controlling blood glucose levels in the elderly with diabetes mellitus with p-value = 0,000 and OR = 56,893. Based on the results of the study, it was found that the implementation of family health tasks has an important role in controlling blood glucose levels on the elderly with diabetes mellitus. The conclusion of this study was there is a significant relationship between the implementation of family health tasks and controlling blood glucose levels on the elderly with diabetes mellitus in Limo Village, Depok.